Why the EU needs to enlarge-with special reference to Turkey’s possible membership and ITS benefits for the EU - Tuza, Gülşah (My University, 2010)
Kurulduğu günden itibaren AB’nin amacı ekonomik bir birlikten önemli güçleri olan siyasi bir oluşuma dönüşmekti. Günümüzde AB dünya’nın en zengin oluşumlarından biri ve uluslararası ilişkiler üzerinde de etki sahibidir. Fakat yine de önemli küresel olaylar üzerindeki etkisi ekonomik gücü ile karşılaştırılamaz. Bunun için de AB çoğunlukla ‘ekonomik bir dev, siyasi bir cüce’ diye tanımlanır. AB’nin kendisi de küresel boyuttaki etkisinin eksikliğinin farkında. Özellikle Avrupa Komisyonu birçok fırsatta bu durumu vurgulamıştır ve AB’nin dünya’da daha stratejik, daha etkili ve daha görünür olması gerektiğinin altını çizmiştir. Bu bağlamda, Türkiye’nin, gerek ekonomik gerekse güvenlik bakımından, Birliğe birçok fayda sağlayabileceği görüşü giderek daha fazla vurgulanmaya başlamıştır. Bu bağlamda, eğer AB 21. yüzyılın getirdiği yeni tehditlerle mücadele edebilen bir aktör olmak ve uluslararası ilişkilerde etkili olmak istiyorsa, Türkiye’nin Birliğe sağlayacağı katkılar çok önemlidir. Ayrıca AB ekonomik anlamda karşılaşacağı uzun vadeli problemlere karşı mücadele etmek istiyorsa Türkiye’nin sağlayacağı katkılar daha da önem kazanmaktadır.

The EU has evolved considerably throughout its history from being an economic entity to a political union with major powers. The EU is today the most prosperous entity of the world and has a great impact on international relations. Nevertheless, the EU’s influence on major global events is not comparable with its economic power. The discourse that the EU is ‘an economic giant, political dwarf and military worm’ is still expressed commonly. It appears that the EU itself is aware of its shortcomings on global issues. Especially the European Commission underlines this on several occasions and stresses that the EU has to become more strategic and more effective and visible around the world. In this context, Turkey’s membership would provide major benefits for the EU, in both economic and security terms. This, however, depends on how influential the EU will become on world affairs. Thus, if the EU is aiming to become an actor that is able to counter the challenges and threats of the 21st century and be influential in international relations, Turkey’s contribution would be of enormous importance. Moreover, if the EU wants to counter long-term problems that it will face in economic issues, Turkey has obviously the potential to contribute.
Keywords: Avrupa Birliği; Ekonomi_Türkiye